Narrow distribution modified silane and method of making and use thereof

CN118852605BActive Publication Date: 2026-10-09JIANGSU QIXIANG HIGH NEW MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410945650.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2026-10-09
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

[0005]针对现有技术中的缺陷,本发明提出了一种窄分布改性硅烷及其制备方法和应用,克服了现有技术中聚醚改性硅烷由于改性过程反应不完全以及催化剂的促进水解硅烷聚合形成凝胶引起的存储稳定性差的缺陷

Benefits of technology

本发明提供的改性硅烷具有高存储稳定性,长时间存储后未发现水解凝胶现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118852605B_ABST
    Figure CN118852605B_ABST
Patent Text Reader

Abstract

The application discloses a narrow-distribution modified silane, a preparation method and application thereof, and the molecular weight distribution of the modified silane is less than 1.30. The specific composite catalyst and specific polyether are used to modify the silane, and the prepared modified silane has a narrow molecular weight distribution and high storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silane coupling agents, and particularly to a narrow-distribution modified silane, its preparation method, and its application. Background Technology

[0002] Silanes are common adhesives and coupling agents, possessing silicon functional groups that react with inorganic components and carbon functional groups that react with organic components. Therefore, they are frequently used for bonding or crosslinking inorganic fillers with resins. In tires, this ability of silanes can reduce the adhesion between fillers, enhance filler dispersion, effectively improve the wet grip and rolling resistance of the rubber compound, and improve the overall performance of the tire.

[0003] Currently, common rubber silane coupling agents include various ethoxy and methoxy silanes. However, these silanes release ethanol or methanol during use, posing significant safety and environmental risks. Therefore, scientists have developed various modified silane products, including those using long-chain alcohols to modify silanes to reduce the release of ethanol or methanol. Furthermore, when modified with polyethers, low rolling resistance and low heat generation can be achieved, breaking the rubber "devil's triangle" to some extent. These modified silanes exhibit superior performance compared to traditional silanes, aligning with the future development direction of green tires and attracting widespread attention.

[0004] However, when using polyether-modified silanes, incomplete reactions can easily occur, leading to polyether residue. Once polyether residue occurs, the hygroscopic nature of the long polyether chains accelerates the hydrolysis of silane. The increased polyether production after silane hydrolysis further accelerates hydrolysis, creating a vicious cycle. Simultaneously, traditional catalysts used for polyether modification can promote the polymerization of hydrolyzed silanes, causing them to form gels and become unusable. This results in extremely poor storage stability of the modified silane. Therefore, there is an urgent need to develop a polyether-modified silane with high storage stability. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention proposes a narrow-distribution modified silane, its preparation method, and its application, overcoming the defects of poor storage stability caused by incomplete reaction during the modification process and the formation of gels due to the promotion of hydrolytic polymerization of silanes by catalysts in existing technologies.

[0006] The present invention provides a polyether-modified silane, wherein the molecular weight distribution of the modified silane is less than 1.30.

[0007] Furthermore, the modified silane has a structure that is one or a mixture of the following general formulas (I) and (II): .

[0008] In this product, the polyether segment of the modified silane is in the middle, and the outer end is a hydrophobic alkyl segment, making the main product hydrophobic.

[0009] Furthermore, in general formulas (I) and (II), R is methyl or ethyl.

[0010] Furthermore, in general formulas (I) and (II), R1 can be the same or different as a straight-chain or branched C1-C12 single-terminated ether chain of polyethylene oxide, polypropylene oxide, or a copolymer of both, including but not limited to C 12 H 25 (OCH2CH2)4-, C 12 H 25 Any one of (OCH2CH2)9-, CH3(OCH2CH2)4-, CH3(OCH2CH2)9-, etc.

[0011] Furthermore, in general formulas (I) and (II), R2 is a straight-chain or branched saturated C1-C10 divalent hydrocarbon group, including but not limited to any one of -CH2-, -CH2CH2-, -CH2CH2CH2-, etc.

[0012] Furthermore, in general formulas (I) and (II), X can be SH, where n=1; S m , where m=2-4, n=2; S(C=O)-R4, where R4 is a straight-chain or branched C1-C12 alkyl group, n=1; H, where n=1.

[0013] The present invention also provides a method for preparing the modified silane, comprising the following steps: After adding silane and polyether to the reaction flask, the main catalyst and co-catalyst are added to the reaction flask at room temperature and stirred for 20-50 min. The temperature is then raised to 60-80℃ and stirred for 30 min (20-50 min). The temperature is then raised to 120-130℃ and vacuum distillation is carried out to distill off the by-product alcohol. After basically no by-product alcohol is distilled off, vacuum distillation is continued for 50-80 min. The co-catalyst is then separated by centrifugation to obtain the polyether-modified silane product. The main catalyst is an organotin catalyst, including but not limited to one or more of dibutyltin dilaurate, stannous octoate, di(dodecyl sulfide)dibutyltin, and dibutyltin diacetate, preferably dibutyltin dilaurate. The amount of the main catalyst is 0.1-1% of the polyether, preferably 0.1-0.5%. The co-catalyst is a halide or oxide of a Group II or Group III metal (Mg, Ca, Sr, Ba, Al, Ge, Ti), including but not limited to one or more of magnesium chloride, aluminum chloride, calcium chloride, magnesium oxide, aluminum oxide, and calcium oxide, preferably magnesium chloride. The amount of the co-catalyst is 0.1-1% of the polyether, preferably 0.1-0.3%. The use of a composite catalyst and a specific polyether alcohol results in high efficiency of the modification process and no polyether residue.

[0014] The polyether is a narrowly distributed monoalkyl polyether alcohol R1-OH with a molecular weight distribution of 1.00-1.17 obtained by anionic ring-opening polymerization, and does not contain large, difficult-to-react polyethers. R1 is a linear or branched C1-C12 single-terminated ether chain of polyethylene oxide, polypropylene oxide, or a copolymer of both. Molecular weight distribution testing method: The test was performed using a Waters GPC instrument, with a liquid chromatography main unit model e2695, a differential refractive index detector main unit model 2414, and chromatographic columns WATERS STYRAGEL HR0.5 (tetrahydrofuran), WATERS STYRAGEL HR2 (tetrahydrofuran), and WATERS STYRAGEL HR1 (tetrahydrofuran), with tetrahydrofuran as the mobile phase.

[0015] Furthermore, the general structural formula of the silane is:

[0016] Wherein, R is methyl or ethyl; R2 is a straight-chain or branched saturated C1-C10 divalent hydrocarbon group; X can be SH, where n=1; S m , where m=2-4, n=2; S(C=O)-R4, where R4 is a straight-chain or branched C1-C12 alkyl group, n=1; H, where n=1.

[0017] Furthermore, the amount of polyether used is 2-4 times the molar equivalent of silane, wherein when n=1, the amount of polyether used is 2 times the molar equivalent of silane, and when n=2, the amount of polyether used is 2-4 times the molar equivalent of silane.

[0018] The present invention also provides the application of the modified silane in tires, particularly in the preparation of molded articles, pneumatic tires, tire treads, hoses, drive belts, seals and shock-absorbing elements, and other components requiring high storage stability. In summary, compared with the prior art, the present invention achieves the following technical effects: The modified silane provided by this invention has high storage stability, and no hydrolysis or gelation phenomenon was found after long-term storage. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a schematic flowchart of the modified silane synthesis method of the present invention; Figure 2 GPC map of AEO4; Figure 3 This is the GPC map of Embodiment 1 of the present invention; Figure 4 The GPC plot is shown in Comparative Example 1; Figure 5 Comparison of GPC spectra for Comparative Example 1 and Example 1; Figure 6 GPC map of AEO9; Figure 7 This is the GPC map of Embodiment 2 of the present invention; Figure 8 The GPC map is shown in Comparative Example 2; Figure 9 Comparison of GPC spectra for Comparative Example 2 and Example 2; Figure 10 GPC pattern of Si69; Figure 11 GPC spectrum of PEG400; Figure 12 This is the GPC map of Embodiment 4 of the present invention; Figure 13 The GPC pattern is shown in Comparative Example 4; Figure 14 Comparison of GPC spectra between Comparative Example 4 and Example 4; Figure 15 This is the GPC map of Embodiment 11 of the present invention. Detailed Implementation

[0021] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0022] Example I. Sources of Raw Materials for Examples and Comparative Examples Unless otherwise specified, all substances used in the embodiments and comparative examples of this invention are commercially available. Among them, the GPC molecular weight distribution of Si69 is 1.00, the molecular weight of Si800 is too small to be within the GPC detection range, the GPC molecular weight distribution of AEO4 is 1.04, the GPC molecular weight distribution of AEO9 is 1.01, the GPC molecular weight distribution of PEG200 is 1.06, and the GPC molecular weight distribution of PEG400 is 1.07.

[0023] The following are the GPC test analysis results of raw materials AE04, AE09, Si69 and PEG-400: AE04: ; AE09: ; Si69: ; PEG-400: .

[0024] II. Performance Tests Storage stability test: Storage stability is determined by hydrolysis verification experiment. Take 60 g of silane sample and put it into a 100 mL beaker. Place it open in a constant temperature and humidity oven. Set the temperature to 40℃ and the humidity to 80%. Record the time when turbidity occurs and when it completely gels (loses fluidity) to determine the hydrolysis rate of the product.

[0025] Example 1 After adding 98 g of trimethoxymercaptopropylsilane and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to a reaction flask, 0.4 g of the main catalyst dibutyltin dilaurate and 0.4 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for another 30 min, and then heated to 120-130 °C. The mixture was then subjected to vacuum distillation to remove the byproduct alcohol. After the byproduct alcohol was almost completely removed, vacuum distillation was continued for 1 h. The co-catalyst was then separated by centrifugation to obtain 426 g of polyether-modified silane product. The results of GPC analysis are as follows: .

[0026] Example 2 After adding 98 g of trimethoxymercaptopropylsilane and 585 g of fatty alcohol polyoxyethylene ether (AEO9) to a reaction flask, 0.6 g of the main catalyst di(dodecylsulfide)dibutyltin and 0.6 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80℃ and stirred for another 30 min, and then heated to 120-130℃. The mixture was then distilled under reduced pressure, and the byproduct alcohol was distilled off. After the byproduct alcohol was almost completely eliminated, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was separated by centrifugation, yielding 643 g of polyether-modified silane product. The results of GPC analysis are as follows: .

[0027] Example 3 After adding 134.7 g of bis-(γ-triethoxysilylpropyl)tetrasulfide and 100 g of polyethylene glycol monomethyl ether (PEG200) to the reaction flask, 0.5 g of the main catalyst di(dodecylsulfide)dibutyltin and 0.1 g of the co-catalyst calcium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for another 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the byproduct alcohol was distilled off. After the byproduct alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was then separated by centrifugation to obtain 201 g of polyether-modified silane product.

[0028] Example 4 After adding 134.7 g of bis-(γ-triethoxysilylpropyl)tetrasulfide and 400 g of polyethylene glycol monomethyl ether (PEG400) to the reaction flask, 0.9 g of the main catalyst dibutyltin dilaurate and 0.4 g of the co-catalyst calcium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80℃ and stirred for another 30 min, and then heated to 120-130℃. The mixture was then distilled under reduced pressure, and the byproduct alcohol was distilled off. After the byproduct alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was separated by centrifugation, and 507 g of polyether-modified silane product was obtained. The results of GPC testing are as follows: .

[0029] Example 5 After adding 98 g of trimethoxymercaptopropylsilane and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to the reaction flask, 1.8 g of the main catalyst dibutyltin dilaurate and 0.4 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was then separated by centrifugation to obtain 419 g of polyether-modified silane product.

[0030] Example 6 After adding 98 g of trimethoxymercaptopropylsilane and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to the reaction flask, 0.4 g of the main catalyst dibutyltin dilaurate and 1.1 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was then separated by centrifugation to obtain 418 g of polyether-modified silane product.

[0031] Example 7 After adding 98 g of trimethoxymercaptopropylsilane and 200 g of polyethylene glycol monomethyl ether (PEG200) to the reaction flask, 0.2 g of the main catalyst dibutyltin dilaurate and 0.4 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was then separated by centrifugation to obtain 262 g of polyether-modified silane product.

[0032] Example 8 After adding 98 g of trimethoxymercaptopropylsilane and 400 g of polyethylene glycol monomethyl ether (PEG200) to the reaction flask, 0.4 g of the main catalyst dibutyltin dilaurate and 0.4 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was then separated by centrifugation to obtain 463 g of polyether-modified silane product.

[0033] Example 9 After adding 98 g of trimethoxymercaptopropylsilane and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to the reaction flask, 0.4 g of the main catalyst dibutyltin diacetate and 0.4 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was then separated by centrifugation to obtain 431 g of polyether-modified silane product.

[0034] Example 10 After adding 98 g of trimethoxymercaptopropylsilane and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to the reaction flask, 0.4 g of the main catalyst dibutyltin dilaurate and 0.4 g of the co-catalyst calcium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was separated by centrifugation to obtain 428 g of polyether-modified silane product.

[0035] Example 11 After adding 134.7 g of bis-(γ-triethoxysilylpropyl)tetrasulfide and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to the reaction flask, 0.8 g of the main catalyst dibutyltin dilaurate and 1.1 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80℃ and stirred for another 30 min, and then heated to 120-130℃. The mixture was then distilled under reduced pressure, and the byproduct alcohol was distilled off. After the byproduct alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was separated by centrifugation, and 466 g of polyether-modified silane product was obtained. The results of GPC testing are as follows: .

[0036] Example 12 After adding 134.7 g of bis-(γ-triethoxysilylpropyl)tetrasulfide and 585 g of fatty alcohol polyoxyethylene ether (AEO9) to the reaction flask, 1.2 g of the main catalyst dibutyltin dilaurate and 1.8 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was then separated by centrifugation to obtain 686 g of polyether-modified silane product.

[0037] Example 13 After adding 98 g of trimethoxymercaptopropylsilane and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to the reaction flask, 3.6 g of the main catalyst dibutyltin dilaurate and 0.4 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was separated by centrifugation to obtain 416 g of polyether-modified silane product.

[0038] Example 14 After adding 98 g of trimethoxymercaptopropylsilane and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to the reaction flask, 0.4 g of the main catalyst dibutyltin dilaurate and 3.6 g of the co-catalyst magnesium chloride were added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the by-product alcohol was distilled off. After the by-product alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h. The co-catalyst was separated by centrifugation to obtain 417 g of polyether-modified silane product.

[0039] Comparative Example 1 After adding 98 g of trimethoxymercaptopropylsilane (Si800) and 365 g of fatty alcohol polyoxyethylene ether (AEO4) to a reaction flask, 0.8 g of dibutyltin dilaurate catalyst was added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80℃ and stirred for another 30 min, and then heated to 120-130℃. The mixture was then distilled under reduced pressure, and the byproduct alcohol was distilled off. After the byproduct alcohol was almost completely eliminated, the mixture was distilled under reduced pressure for 1 h to obtain 430 g of polyether-modified silane product. The GPC analysis results are as follows: .

[0040] Comparative Example 2 After adding 98 g of trimethoxymercaptopropylsilane and 585 g of fatty alcohol polyoxyethylene ether (AEO9) to a reaction flask, 1.2 g of di(dodecyl sulfide)dibutyltin catalyst was added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80℃ and stirred for another 30 min, and then heated to 120-130℃. The mixture was then distilled under reduced pressure, and the byproduct alcohol was distilled off. After almost no byproduct alcohol was distilled off, the mixture was distilled under reduced pressure for 1 h to obtain 648 g of polyether-modified silane product. The results of GPC testing are as follows: .

[0041] Comparative Example 3 After adding 134.7 g of bis-(γ-triethoxysilylpropyl)tetrasulfide (Si69) and 100 g of polyethylene glycol monomethyl ether (PEG200) to the reaction flask, 0.6 g of the catalyst di(dodecyl sulfide)dibutyltin was added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80 °C and stirred for 30 min, and then heated to 120-130 °C. The mixture was then distilled under reduced pressure, and the byproduct alcohol was distilled off. After the byproduct alcohol was basically no longer distilled off, the mixture was distilled under reduced pressure for 1 h to obtain 202 g of polyether-modified silane product.

[0042] Comparative Example 4 After adding 134.7 g of bis-(γ-triethoxysilylpropyl)tetrasulfide and 400 g of polyethylene glycol monomethyl ether (PEG400) to a reaction flask, 1.3 g of dibutyltin dilaurate catalyst was added to the reaction flask at room temperature. The mixture was stirred for 30 min, heated to 80℃ and stirred for another 30 min, and then heated to 120-130℃. The mixture was then distilled under reduced pressure, and the byproduct alcohol was distilled off. After almost no byproduct alcohol was distilled off, the mixture was distilled under reduced pressure for 1 h to obtain 498 g of polyether-modified silane product. The GPC analysis results are as follows: .

[0043] The molecular weight distributions of the modified silanes obtained in Examples 1-14 and Comparative Examples 1-4 are shown in Table 1 below: Table 1. Molecular weight distribution of modified silanes in the examples and comparative examples project Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 <![CDATA[M w / M n ]]> 1.17 1.08 1.25 1.22 1.18 1.16 1.20 1.19 1.20 1.23

[0044] The modified silanes of Examples 1-14 and Comparative Examples 1-4 were subjected to storage stability tests. 60 g of silane sample was placed in a 100 mL beaker and left uncovered in a constant temperature and humidity oven at 40°C and 80% humidity. The time to turbidity and complete gelation (loss of fluidity) was recorded to determine the hydrolysis rate of the product. The results are shown in Table 2. Table 2. Hydrolysis test results of modified silanes in the examples and comparative examples

[0045] From Table 1-2 and Figure 2-15It is evident that the modified silanes obtained through this invention have molecular weight distributions all below 1.30 and exhibit high storage stability. Under high humidity conditions (40°C and 80%), the product experiences turbidity for over 120 hours, generally over 240 hours, and complete gelation for over 240 hours, generally over 720 hours. This demonstrates that the modified silanes obtained through the formulation and preparation method of this application overcome the shortcomings of poor storage stability in existing technologies, exhibiting significant advantages compared to comparative examples, and effectively meeting the high standards required by customers and the market.

[0046] Compared with Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4, no composite catalyst was added during the modification process. The molecular weight distribution of the modified silanes prepared was too large, resulting in extremely poor product storage performance in a high humidity environment of 40°C and 80%.

[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A polyether-modified silane, characterized in that, The polyether-modified silane has a molecular weight distribution of less than 1.30; the polyether-modified silane is prepared from raw materials comprising the following components: Silanes, polyethers, main catalysts, and co-catalysts; The general structural formula of the silane is: Wherein, R is methyl or ethyl; R2 is a straight-chain or branched saturated C1-C10 divalent hydrocarbon group; X is SH, where n=1; or X is S m Where m=2-4, n=2; or X is SC(=O)-R4, where R4 is a straight-chain or branched C1-C12 alkyl group, n=1; or X is H, where n=1; The main catalyst is an organotin catalyst, and the co-catalyst is a halide or oxide of a Group 2 or Group 3 metal. The polyether is a narrowly distributed monoalkyl polyether alcohol R1-OH with a molecular weight distribution of 1.00~1.17 obtained by anionic ring-opening polymerization, where R1 is a straight-chain or branched C1-C12 single-terminated ether chain of polyethylene oxide, polypropylene oxide, or a copolymer of both.

2. The polyether-modified silane according to claim 1, characterized in that, The polyether-modified silane has a structure that is one or a mixture of the following general formulas (I) and (II): 。 3. The polyether-modified silane according to claim 2, characterized in that, In general formulas (I) and (II), R is methyl or ethyl.

4. The polyether-modified silane according to claim 2, characterized in that, In general formulas (I) and (II), R1 is the same or different as a straight-chain or branched C1-C12 single-terminated polyethylene oxide, polypropylene oxide, or an ether-based chain of both copolymerized.

5. The polyether-modified silane according to claim 2, characterized in that, In general formulas (I) and (II), R2 is a straight-chain or branched saturated C1-C10 divalent hydrocarbon group.

6. The polyether-modified silane according to claim 2, characterized in that, In general formulas (I) and (II), X is SH, where n=1; or X is S. m Where m=2-4, n=2; or X is SC(=O)-R4, where R4 is a straight-chain or branched C1-C12 alkyl group, n=1; or X is H, where n=1.

7. The method for preparing the polyether-modified silane according to any one of claims 1-6, characterized in that, Includes the following steps: Silane, polyether, main catalyst and co-catalyst are added to a reaction vessel and stirred evenly. The temperature is increased and stirring is continued until the materials are thoroughly mixed. The temperature is then increased and vacuum distillation is carried out. After no by-product alcohol is distilled out, vacuum distillation is continued for 1-2 hours to separate the co-catalyst and obtain the polyether-modified silane.

8. The preparation method according to claim 7, characterized in that, The amount of polyether used is 2-4 times the molar equivalent of silane.

9. The use of the polyether-modified silane according to any one of claims 1-6 in tires.

Citation Information

Patent Citations

  • Silane coupling agent containing vinyl ether chain segment, and preparation method and application thereof

    CN106674593A

  • Preparation method of reactive sealant resin

    CN111378107A